Azerbaycan'da dijital televizyon yayıncılığının alternatif medyayı geliştirmesi sürecinde II. Karabağ Savaşı - Samadli, Nigar (My University, 2025)
Dijitalleşme süreciyle birlikte medyanın yeni yayıncılık sistemine geçiş yapması, hemen hemen bütün kitle iletişim araçlarına yeni özellikler kazandırmıştır. Bütün alanlarda olduğu gibi televizyon da internetin sağladığı olanaklarla dijital yayıncılığa geçiş yapmıştır. Her zaman popülaritesini koruyan televizyon, dijitalleşme sürecinin kazandırdığı etkileşim özelliğiyle izleyicilere yeni olanaklar sunmuştur. Sosyal medya mecralarının ortaya çıkmasıyla televizyon yayıncılığı daha interaktif hale gelmiştir. İzleyicilerin de birer içerik üreticisine dönüştüğü bu ortamda, alternatif medya sıkça duyulan kavramlardan biri olmuştur. Bu bağlamda, ele alınan bu tez çalışmasında Azerbaycan`da televizyon yayıncılığının dijitalleşmesi süreciyle birlikte alternatif medyanın gelişimi konusu incelenmiştir. Özellikle İkinci Karabağ Savaşı döneminin irdelendiği çalışmada, o dönem yayıncılık yapan 15 kişiyle derinlemesine görüşmeler gerçekleştirilmiş, elde edilen bulgularla ülkede alternatif medyanın güncel durumu ortaya koyulmuştur. Savaş ve barış gazeteciliği kavramlarının karşılaştırmalı olarak incelendiği bu araştırmanın, ileride alanda yapılacak olan çalışmalara ve akademik kaynaklara katkı sağlayacağı düşünülmektedir.

With the process of digitalisation, the transition of media into a new broadcasting system has endowed almost all mass communication tools with new features. As in all fields, television has also embraced digital broadcasting through the opportunities provided by the internet. Maintaining its popularity over time, television has offered new possibilities to audiences through the interactive features brought about by digitalization. With the emergence of social media platforms, television broadcasting has become increasingly interactive. In this new environment, where viewers have also transformed into content creators, the concept of alternative media has become frequently discussed. In this context, the present thesis examines the development of alternative media in parallel with the digitalization of television broadcasting in Azerbaijan. The study particularly focuses on the period of the Second Karabakh War, during which in-depth interviews were conducted with 15 individuals active in broadcasting at the time. The findings obtained from these interviews reveal the current state of alternative media in the country. By comparatively analyzing the concepts of war journalism and peace journalism, this research is expected to contribute to future studies in the field and serve as a valuable academic resource.
The second Karabakh War in the process of developing alternative media in digital television broadcasting in Azerbaijan
Keywords: 20. yy; 20th century; Alternatif Medya; Alternative Media; Azerbaijan; Azerbaycan; Barış Gazeteciliği; Dağlık Karabağ (Azerbaycan); Digital Publishing; Digital television; Dijital televizyon; Dijital Yayıncılık; History; İkinci Karabağ Savaşı; Nagorno-Karabakh (Azerbaijan); Peace Journalism; Second Nagorno-Karabakh War; Tarih; Technological innovations; Teknolojik yenilikler; Television broadcasting; Televizyon yayıncılığı